1997
DOI: 10.1002/(sici)1098-2736(199704)34:4<399::aid-tea8>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Light propagation and visual patterns: Preinstruction learners' conceptions

Abstract: This study formed part of a project aimed at revising the instructional approach for geometrical optics in the 10th grade. The instructional intervention was based on the extensive use of a diagrammatic representation as a descriptive, explanatory, and problem-solving tool in the domain. The purpose of this study was to elicit the conceptions and representations of light propagation, image formation, and sight typical to preinstruction learners, with special attention to identifying precursors of problematic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…7,12 Students are better able to interpret the propagation of light when they consider it independently of sight. 20 While extending one's vision is the purpose of using a telescope, it is possible to investigate the interaction of the telescope with light without tackling how the eye sees.…”
Section: Learning Opticssupporting
confidence: 91%
“…7,12 Students are better able to interpret the propagation of light when they consider it independently of sight. 20 While extending one's vision is the purpose of using a telescope, it is possible to investigate the interaction of the telescope with light without tackling how the eye sees.…”
Section: Learning Opticssupporting
confidence: 91%
“…While there is a rich literature on students' conceptions (Duit 2009), science educators have realized that teachers do not have many , 1983;Fetherstonaugh and Treagust 1992;Galili and Hazan 2000;La Rosa et al 1984;Langley et al 1997). Thus, using TTMC items affords teachers access to results of this literature for uncovering students' pre-instructional understanding and reasoning about the phenomena or concepts.…”
Section: Development and Analysis Of Two-tier Itemsmentioning
confidence: 99%
“…Developing TTMC items draws on literature on students' alternative conceptions that have been conducted over the past 20 years or so. For example, Chu and Treagust (2009) developed the Light Propagation Diagnostic Instrument (LPDI) based on prior qualitative research studies on students' conceptions mainly about fundamental geometric optics (Andersson and Kärrqvist, 1983;Fetherstonaugh and Treagust 1992;Galili and Hazan 2000;La Rosa et al 1984;Langley et al 1997). Thus, using TTMC items affords teachers access to results of this literature for uncovering students' pre-instructional understanding and reasoning about the phenomena or concepts.…”
Section: Development and Analysis Of Two-tier Itemsmentioning
confidence: 99%
“…At the upper-level high school and undergraduate levels, research has also been conducted on how students understand and apply the basic physical properties of light. Langley et al 3 showed that while students had some familiarity with optical systems, they were confused by a unified model of optics in which the context of sight was discussed. Saxena 4 found that while students seemingly understood the basic properties of light, they were unable to apply that knowledge to real situations.…”
Section: A Student Understanding Of Light and Opticsmentioning
confidence: 99%